Geriatric Learning Questionnaire for Clinician-Educators (G-CEL-Q) (Out of Print) - EunMi Park; Colleen Christmas; Samuel Durso (Association of American Medical Colleges, 2007)
Abstract Introduction To meet the goal of strengthening faculty expertise in geriatrics, four leading geriatrics institutions formed a consortium in July 2004. A member of the consortium, the Johns Hopkins University Division of Geriatric Medicine and Gerontology (JHUDGMG), produced the Geriatrics Clinician-Educator Learning Questionnaire (G-CEL-Q) to assess the self-reflected beliefs and attitudes of nongeriatrician faculty toward teaching in geriatrics as a measure of the impact of an intensive course on forming their behavioral intentions to teach in geriatrics. Literature in behavioral science suggests that positive beliefs and attitudes are necessary preconditions for producing desired intentions and behaviors. Intensive course formats can yield effective learning results if participants have positive responses to the course experience. Methods G-CEL-Q assessment areas include perceived knowledge (K), perceived value of learning subject matter for practical use (V), perceived confidence to teach selected subject areas (C), and interest in learning skills to teach the selected subject areas (I), which are factors associated with the likelihood of developing and implementing a teaching plan in a diverse group of teachers. Fifteen subject areas in geriatric principles and educational guidelines for clinician-teachers were selected by 21 content experts, all physician faculty at JHUDGMG. These areas were beta tested in May 2005 and further refined. Results Since May 2005, the tool has been used with three cohorts of the Donald W. Reynolds Faculty Development to Advance Geriatric Education Mini-Fellowship. A test of version 1.0 conducted in June 2005 (n = 23) suggested that the visual presentation of the response system for the assessment domain areas (K, V, C, and I) needed to be improved by creating separate columns. Therefore, visual presentation was updated for version 2.0. Groups using version 2.0 were tested independently in May 2006 (n = 23) and September 2006 (n = 10) to determine scale and domain reliability. For scale reliability, Cronbach's alpha coefficients for test and retest after a 3-day interval were .928 and .945 for May 2006 and .958 and .947 for September 2006 (n = 10). For domain reliability, the alphas for test and retest after a 3-day interval were as follows: K: .888 and .817 (May 2006), .917 and .894 (September 2006); V: .907 and .899 (May 2006), .845 and .839 (September 2006); C: .863 and .879 (May 2006), .913 and .899 (September 2006); and I: .886 and .905 (May 2006), .919 and .875 (September 2006). Discussion In a pre-post assessment design, the G-CEL-Q was useful not only for examining a new educational program's efficacy in enhancing beliefs and attitudes of nongeriatrician faculty toward teaching geriatric principles but also for identifying areas in which participants would be likely to benefit from mentoring in order to retain and develop their intention to teach and their teaching behaviors after a formal intensive course.